Effect of Niobium Addition on The Morphological Behaviour of Au tempered Ductile Iron - K Alias, S.; N. Halmy, M.; A. Mat Shah, M.; Abdullah, B.; H. Ismail, M.; F Idham, M. (International Journal of Engineering and Technology, 2018)
This paper investigate the effect of niobium addition at 0.5 wt% to the morphological behavior of austempered ductile iron. Austempered ductile iron (ADI) and niobium alloyed austempered ductile iron was prepared by first austenitizing the samples at 900Â°C before austempering process was conducted in salt bath at 1 hour holding time. The samples were then cooled to room temperature. The microstructural observation and analysis in term of nodule count, nodularity percentage and graphite percentages were conducted using Olympus B X 41M microscope with IMAPs 4.0 edition, Scanning electron microscopy (SEM) analyzer using SMARTSEM software and energy-dispersive X-Ray (EDX) spectroscopy. It was found that addition of niobium resulting in formation of niobium carbide (NbC) and much finer retained austenite and acicular ferrite structure.However,the nodularity, nodule count and graphite area were reduced due to the presence of niobium carbide.Â